SURVEI TEKNIK DASAR DAN KONDISI FISIK PADA SISWA SEKOLAH SEPAK BOLA (SSB) SE KABUPATEN DEMAK TAHUN 2012 (Department of Physical Education, Sport, Health and Recreation, 2013)
Good physical condition and primed and ready to face an opponent playing an important element in the gameof football as well as a good basic technique will support a good game. Issues raised in this research is how thebasic techniques and the physical condition of the student School Football (SSB) in Demak 2012. The purposeof this study was to determine the basic engineering and the physical condition of the student School Football(SSB) in Demak 2012. The population in this study were all students at 14 schools football (SSB) 2012. In thisstudy a total sampling using purposive sampling that all student populations School Football (SSB) in Demakregency. In a study variable is the physical condition and basic movement skills to play soccer. To obtain theappropriate data in this study using survey methods and testing techniques. To the physical condition of thevarious tests used are: sprint (sprint) 50 meters, gantungsiku bend, sit-ups 60 seconds, vertical jump (verticaljumping), and run a distance of 1000 meters. As for the basic motor skills to play football, the various tests usedwere: test football and hold the ball (passing and stoping), test play ball with the head (heading), test dribbling(dribbling), and a test shoot / kick ball to target (shooting). Based on the calculation of descriptive percentageof overall physical condition known football school students (SSB) se Demak it can be concluded that theoverall physical condition of the football school students (SSB) as most of Demak 60 (60%) of students includedin the category being. . To test the basic movement skills soccer soccer school students (SSB) se Demak note that74 (74%) of students included in both categories. Some researchers suggest among other things that the playersshould have a training program that unplanned well supported with regular matches. In providing physicalexercise and basic movement skills that can be more easily understood and controlled by the player, then theprovision of this training should be given at an early age. In the implementation of the exercise of the playersshould not abandon the principles of exercise include the addition of weights, repetitions, increase, adjusted forsports branch and have a target.